2022
DOI: 10.3389/fpsyg.2022.795117
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Outcome vs. Process Accountability-Focus on Performance: A Meta-Analysis

Abstract: BackgroundThe foundation of a safe practice is accountability, especially outcome- rather than process-focused accountability, particularly during pandemics such as COVID-19. Accountability is an essential behavior that promotes congruence between nursing actions and standards associated with quality of care. Moreover, the scant research examining whether one accountability focus is superior in motivating humans to better task performance yields inconclusive results.AimsSystematically examine the effect of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
1
1
1
Order By: Relevance
“…Our finding supports several previous studies demonstrating that process accountability better suits complex tasks and that outcome accountability better suits simpler tasks (Hall et al, 2017; Patil et al, 2014, 2017). However, the results also contradict those of a recent meta‐analysis (Sharon et al, 2022) demonstrating that under process accountability, simple tasks were performed more precisely, and that under outcome accountability, complex tasks achieved better results. These conflicting findings may be explained by how complex tasks are defined and operationalized.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Our finding supports several previous studies demonstrating that process accountability better suits complex tasks and that outcome accountability better suits simpler tasks (Hall et al, 2017; Patil et al, 2014, 2017). However, the results also contradict those of a recent meta‐analysis (Sharon et al, 2022) demonstrating that under process accountability, simple tasks were performed more precisely, and that under outcome accountability, complex tasks achieved better results. These conflicting findings may be explained by how complex tasks are defined and operationalized.…”
Section: Discussioncontrasting
confidence: 95%
“…First, our findings supported recent studies indicating that there is no superior accountability‐focus mechanism that motivates workers to higher performance (Davis et al, 2007; Häusser et al, 2017; Sharon et al, 2022). Yet, our findings indicated that the impact of an accountability focus on performance critically depends on the type of task performed through the mediation of strain.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation